Óleo de macadâmia e Vitamina E para cordeiros: qualidade da carne, perfil de ácidos graxos e expressão gênica - Dias Junior, Paulo César Gonzales (2019)
This work assessed the effects of Macadamia Oil (MO) and Vitamin E supplementation on lambs in different feeding managements about physico-chemical and sensory quality of meat, fatty acid profile and gene expression. Sixty lambs (n=10) were divided into factorial 2x3, two feeding systems, feedlot and pasture, with three experimental supplements (control, with MO, and with MO + Vitamin E). Meat fat increased 31% in feedlot animals and 20% in animals that received MO independently of vitamin E (P < 0, 05). The animals on pasture improved their polyunsaturated fatty acid proportions (PUFA) omega 3 (n3) and decreased the atherogenicity level of meat. The supplementation with MO with or without Vitamin E increased the amount (mg/100g) of PUFA n3, but also increased fatty acids C14:0, C16:0 and C18:0 (P < 0, 05). The supplementation with MO and Vitamin E increased C18:3 n3 proportion in the muscle and improved meat flavor (P>0, 05). The use of MO without Vitamin E improved texture and global meat impression parameters (P < 0, 05). The supplements containing Macadamia and Vitamin E increased the expression of the gene SCD-1 and ELOVL6 (P < 0, 05).